Translating and Evaluating a Physical Activity Program for Aboriginal Elders on Noongar Boodjar (Country) — A Longitudinal Study - Gidgup, Margaret J. R.; Kickett, Marion; Jacques, Angela; Weselman, Tammy; Hill, Keith D.; Coombes, Julieann; Ivers, Rebecca; Bowser, Nicole; Palacios, Vilma; Hill, Anne-Marie (Frontiers in Public Health, 2022)
Abstract Objective: The primary aim of the study was to translate and evaluate the impact of a Physical Activity (PA) program on the physical function of older Aboriginal Elders on Noongar Boodjar (Country). Methods: A longitudinal design framed within an Indigenous methodology. Two groups, one metropolitan and one regional, of Aboriginal Elders, aged ≥45 years, participated in the Ironbark PA program. This comprised weekly strength and balance exercises followed by yarning circles. Physical function (primary outcome) and functional ability, cardiovascular risk factors (weight, waist circumference), falls efficacy and health-related quality of life were measured at baseline 6, 12 and 24 months. Data were analyzed using generalized linear mixed effects modelling. Results: Fifty-two Elders initially enrolled and of those, n= 23 (44.2%) Elders participated regularly for 24 months. There was a 6-month gap in program delivery due to the COVID-19 pandemic. Participants made significant improvement in physical function at 12 months compared to baseline: [short physical performance battery (SPPB) at baseline, 8.85 points (95% CI 8.10, 9.61); 12 months 10.28 (95% CI 9.44,11.13), p=0.001: gait speed at baseline 0.81 ms-1 (95% CI 0.60,0.93); 12 months 1.14 (95% CI 1.01,1.27), p<0.001]. Some sustained improvement compared to baseline was still evident at 24 months after the 6-month gap in attendance [SPPB 9.60 (8.59,10.60) p=0.14, gait speed 1.11 (0.95,1.26) p<0.001]. Cardiovascular risk factors showed a non-significant improvement at 12 and 24 months compared to baseline. All participants reported that they enjoyed the program, found it culturally appropriate and would recommend it to others. Conclusion: Older Aboriginal people showed sustained improvements in physical function after engaging in a culturally appropriate PA program. Culturally appropriate PA programs provide safety, security and choice for older Aboriginal people to engage in evidence-based PA. Funding This study was funded by a Healthway Grant (grant number 31960). MJRG is a Noongar Wadjuk PhD student supported by a stipend from the grant. AMH is supported by a National Health and Medical Research Council of Australia Investigator (EL2) award.